Effects of concept mapping and guided discovery instructional strategies on students’ achievement in redox concept of chemistry in Oyo State, Nigeria (2022)
The study determined the effects of concept mapping and guided discovery instructional strategies on student’s learning achievement in Redox concept in Chemistry in Oyo State, Nigeria. The pretest-posttest control group quasi experimental design with 3x2 factorial matrix was adopted, while six schools with one intact class each; two each for experimental groups and two for control group were used. A total of 176 senior secondary school 2 Chemistry students participated in the study. A validated Chemistry Student Achievement Test (r = 0.77) was used for data collection, while Analysis of covariance and Bonferroni post hoc were used to analyze the data collected at 0.05 level of significance. There was a significant main effect of treatment (F(2, 175) =11.84; p<0.05, partial η2 = 0.13) on student’s achievement. The participants in concept mapping strategy obtained the highest post achievement mean score (12.71), followed by guided discovery instructional strategy (9.24) and conventional strategy (8.60) groups. There was no significant main effect of gender on student’s achievement. There was no significant two- way interaction effect of treatment and gender on student’s achievement in Redox concept of chemistry. Concept mapping and guided discovery instructional strategies enhanced student’s achievement in Redox concept of chemistry. It is therefore recommended that chemistry teachers should adopt these strategies to improve student’s achievement in Chemistry.